The Effect of Learners’ Sponsorship on Students’ Retention in USE Schools in Bugisu Sub Region - Mwenyi, Davis Caxton Mandu; Buyera, Geofrey (East African Journal of Arts and Social Sciences, 2025)
Student retention in secondary education remains a significant concern, particularly in developing countries like Uganda, where socio-economic barriers impede access to education. The introduction of Universal Secondary Education (USE) in Uganda in 2007 aimed to address these challenges by providing free secondary education, but retention rates remain low due to ongoing financial burdens. This study explored the impact of learners' sponsorship, particularly through government-sponsored programs like USE, on student retention in secondary schools in Bugisu Sub Region, Uganda. Using a mixed-methods approach, including quantitative surveys, qualitative interviews, and focus group discussions, the research examined the role of financial support and parental involvement in influencing retention. The findings reveal that government sponsored education significantly improves student retention, with fee exemptions and supplementary financial support contributing to increased enrolment and regular attendance. However, challenges such as the need for further financial support for additional costs (e.g., transportation, meals) remain. The study concludes that while government initiatives like USE have had a positive impact, there is a need for enhanced investment in expanded financial support, and increased parental engagement to further improve retention rates. These findings offer valuable insights for policymakers and educators aiming to improve secondary education retention in similar contexts.